Developmental ideotype in the context of the dual‐purpose use of triticale, barley and durum wheat. (27th October 2014) - Giunta, F.; Motzo, R.; Fois, G.; Bacciu, P.
Abstract Phenology strongly affects the performance of dual‐purpose (forage plus grain) cereals by defining the rate of leaf and tiller appearance, the duration of the pre‐grazing period and anthesis date. Here, the combined effect of genotypic and environmental variation conditions on anthesis date and the pre‐grazing period in durum wheat, triticale and barley was analysed to define a developmental ideotype for their dual‐purpose use. The extensive variation for the Haun stage reached at the time of apex emergence from the soil surface was associated with variation in the final leaf number, regardless of environment, species and cultivar. The timing of the terminal spikelet stage was the best predictor of apex emergence. The durum wheats tillered poorly, whereas the barleys and the triticales performed comparably in three of the four environments. In general, the higher the final leaf number, the higher the number of leaves and tillers produced by the time of apex emergence, the higher the number of leaves which emerges subsequently. The development of a high number of leaves both before and after apex emergence is advantageous, provided that anthesis is not overly delayed such that flowering and grain fill occur within a period where stressful conditions are likely to occur. Barley developed many leaves and had a low phyllochron, so was identified as the species with the development best suited for dual‐purpose cropping. However, the near simultaneous emergence of the first two tiller apices exposes it to a risk of grazing damage.